Exploring the association of addiction-related genetic factors with non-suicidal self-injury in adolescents - Guo, Zhichao; Liu, Yilin; Wang, Chengjuan; Li, Shujun; Yu, Lei; Wu, Wenzhi; You, Xu; Zhang, Yunqiao; Teng, Zhaowei; Zeng, Yong (Frontiers in Psychiatry, 2023)
Background: Non-suicidal self-injury (NSSI) is self-injurious behavior without suicidal intent commonly seen in the adolescent population and poses a serious threat to the life safety of adolescents. Related researches suggest a possible correlation between addiction and the occurrence of NSSI. This study aimed to explore the correlation between addiction and NSSI from a molecular biological perspective by analyzing the differential expression of addiction-related genes in NSSI patients. Methods: (1) The association between addiction and non-suicidal self-injury in a Chinese adolescent population was verified with the help of questionnaires on substance and behavioral addictions and non-suicidal self-injury among 1329 adolescents in China. (2) Screening for key genes associated with addiction by bioinformatics analysis. (3) RT-qPCR experiment was performed to validate key genes and Receiver Operating Characteristic curves were plotted for target genes. Results: (1) Substance and behavioral addictions were all significantly correlated with non-suicidal self-injury. (2) Four target genes: SERPINA3, SLC14A1, RPS6 and RPS3A were screened by bioinformatics technique. (3) Relative quantitative analysis by RT-qPCR revealed that the expression levels of SLC14A1 (p<0.01), RPS6 (p<0.05) and RPS3A (p<0.01) were significantly higher in NSSI patients than in healthy controls. Conclusion: (1) The significant association between addiction and NSSI exists in the Chinese adolescent population. (2) Addiction-related genes SLC14A1, RPS6, and RPS3A are differentially expressed in adolescents with NSSI. The genes have the potential to become biological markers for the diagnosis of NSSI.